Pruning time for blackberry in the subtropical region - Leonel, Sarita [UNESP] (2015)
It is known that fruits offered out of the harvest peak have higher prices. In southern states in Brazil, where the largest area of cultivation is found in the country, the climate is temperate and the harvest season for blackberry is from November to February. The study aimed at staggering the blackberry harvest by performing the winter pruning at different times in the subtropical conditions of São Paulo state, taking into account the agricultural performance and the crop phenology. The experiment was conducted at the São Manoel Experimental Farm, São Manuel city-SP. Four-year old plants of blackberry “Tupy cultivar were used and trained in T- espalier using 4 main stems at 1.2m high. The experimental design was randomized blocks with four replicates and 5 treatments (pruning times: 30/05, 27/06, 22/07, 24/08 and 27/09), and 5 plants per plot. The results showed that it was possible to extend the harvest period, regardless the irrigation use. However, very early pruning affected crop yield, being August and September the best season for pruning.